Optimizing Spiritual Leadership for the Development of Islamic Education in Madrasah - Wahib, Abd. (Journal of Educational Management Research, 2025)
The purpose of this paper is to examine the optimization of spiritual leadership in the development of Islamic education in a madrasah. This study employs a qualitative case study approach. Data collection methods include participant observation, in-depth interviews, and documentation. The data analysis methods employed are data condensation, data presentation, and conclusion. The findings of this study indicate that: (1) The spiritual leadership of the principal has been implemented effectively, primarily through the application of the values ​​of integrity (siddiq), trustworthiness (amanah), open human relations (fathanah), and innovative work (tabligh) in the school environment. The optimization of spiritual leadership in the development of Islamic education is reflected in the instillation of values that are not solely oriented towards worldly life, but also towards the afterlife. Thus, both the principal and teachers carry out their duties not only as administrative and instructional obligations, but as a form of devotion to Allah SWT.